2021
DOI: 10.3390/ani11030595
|View full text |Cite
|
Sign up to set email alerts
|

Association between Experience of Pet Ownership and Psychological Health among Socially Isolated and Non-Isolated Older Adults

Abstract: The psychological health effects of pet ownership have been widely studied, but only a few studies investigated its impact among socially isolated older adults. The present study aims to investigate the psychological health of older adults with or without the experience of pet (i.e., dog or cat) ownership who are socially isolated or not socially isolated. This study used cross-sectional data from 9856 community-dwelling older adults in a metropolitan area of Japan. Social and non-social isolation and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 32 publications
0
30
0
4
Order By: Relevance
“…In future work it will be important to consider the psychological pathways that may link dog ownership to reduced disability onset. A recent study reported that dog ownership improves the psychological well-being of socially isolated older adults [ 31 ]. It is known that psychological well-being is inversely related to the onset of frailty [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In future work it will be important to consider the psychological pathways that may link dog ownership to reduced disability onset. A recent study reported that dog ownership improves the psychological well-being of socially isolated older adults [ 31 ]. It is known that psychological well-being is inversely related to the onset of frailty [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that having a dog may be particularly beneficial when owners regularly walk them. Dog walking has been implicated as a means to increase opportunities for social interaction and improve psychological health for older adults [10]. Older adult dog owners who are socially isolated may be motivated to walk their dogs, offering several downstream positive effects likely to reduce loneliness such as increased physical activity, improved mental health, and increased opportunities for social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Relating to psychological and social benefits, recent studies suggest that pet ownership may improve well-being, life satisfaction, and happiness, as well as decrease loneliness and social isolation, depressive symptoms, and anxiety [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. It may also increase levels of physical activity and/or walking of older adult pet owners [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%